Cellular repressor of E1A-stimulated genes inhibits inflammation to decrease atherosclerosis in ApoE−/− mice. (September 2015) - Sun, Mingyu; Tian, Xiaoxiang; Liu, Yanxia; Zhu, Nan; Li, Yang; Yang, Guitang; Peng, Chengfei; Yan, Chenghui; Han, Yaling
Abstract: Aims: Macrophage inflammation response is important in the pathogenesis of atherosclerosis. We investigated the role and mechanism of cellular repressor of E1A-stimulated genes (CREG) in regulating TNF-α induced inflammation response in macrophages and explore whether CREG might be a therapeutic target for atherosclerosis. Method and results: Immunostaining and western blotting showed that expression of CREG was reduced in human atherosclerotic coronary artery. In vivo experiments demonstrated that supplementation of recombinant CREG protein to ApoE −/− mice fed with high fat diet alleviated aortic atherosclerosis development and inflammation. In vitro, macrophage from ApoE −/− mice fed with high fat diet had lower level of CREG compared to control mice fed with normal diet. Immunohistochemical staining and western blotting further confirmed that CREG inhibited inflammatory response of macrophages induced by TNF-α. Supplementation of exogenous recombinant CREG protein or CREG gene silencing showed that CREG promoted autophagy in TNF-α treated macrophages. The use of autophagy inhibitors, 3-methyladenine and bafilomycin A, identified that CREG attenuated TNF-α induced inflammation by activate autophagy. In addition, supplementation of exogenous CREG protein stimulated expression and maturity of cathepsin B and cathepsin L and induced lysosome formation, whereas CREG deficiency reduced lysosomal formation. Conclusion: CREG inhibits inflammation and promotes autophagy mediated by lysosome formation; it might be a potential therapeutic target in atherosclerosis. Highlights: CREG1 inhibits atherosclerosis by reducing the macrophage inflammation in ApoE −/− mice. CREG inhibits macrophage inflammation and promotes autophagy by regulating lysosome biogenesis. CREG may represent a new therapeutic target against atherosclerosis.